'To see a world in a grain of sand' : glass from Nubia and the ancient Mediterranean - Spedding, Juliet V., (Archaeopress Archaeology, 2023)
Using modern scientific methods, this book examines glass beads and vessel fragments dating from the Meroitic and Early Nobadia periods, providing a new assessment of glass from Nubia. Results reveal interrelationships between trade, technological understanding, and manufacturing choices across the cultures of Sudan, Egypt and the Mediterranean.